Supervisors' opinion regarding the situation of postgraduate fellowship training in Gynaecology and Obstetrics of selected medical colleges in Bangladesh (Bangladesh Journal of Medical Education, 2017)
Background: Worldwide , the modernization of medical education is leading to the design and implementation of new postgraduate curricula. The necessity to reform postgraduate medical education has been recognized worldwide. Grounding in educational science and social accountability are raising issues.Objective: To analyze the situation of the fellowship (FCPS, Part-II) training in Gynaecology & Obstetrics of selected medical colleges in Bangladesh.Methodology: This descriptive type of cross sectional study was conducted among 50 supervisors of Obstetrics & Gynae dept. at selected medical colleges four in Dhaka city and four outside Dhaka. This study was carried out from January to December, 2014. The sampling technique was convenient sampling. In-depth interview of the supervisors was taken.Results: During interview majority (60%) of the supervisors told that the curriculum is followed in Obs & Gynae Part 11 course which is made by BCPS is standard. About 80% supervisors told that the institution has well developed infrastructure, academic complex and OT complex for training and 70% told that there are well organized investigation facilities and instruments available. Majority of the supervisors (80%) told that supervisors and trainees ratio is proper. Majority of the supervisors (75%) told that training is full time and residential. Majority of the supervisors (95%) told that patient care services (outdoor, indoor and emergency) are satisfactory. About 80% supervisors told that they have not good library facilities with latest books and journals. Internet/website facilities are also not available in all libraries. Most of the supervisor (80%) respondents believed that their hospital should have a mechanism for consultation, feedback and supervisory assessments system.Conclusion: So significant room exists for improvement in the quality of fellowship training as indicated by the less than desirable proportion of trainees being satisfied with different aspects of training. Faculty members who constitute the cornerstone of educational process are pivotal to effect the desired improvements.Bangladesh Journal of Medical Education Vol.6(1) 2015: 8-11